Determinants of Investment Implementation Barriers In South Sulawesi Province - Hernawan, Hernawan (Universitas Negeri Makassar, 2023)
This research aims to study and analyse the determinant factors that become obstacles in the implementation of investment in South Sulawesi Province. The research method used is descriptive qualitative research supported by several data such as observation data, interviews and policy documents. The results showed that the determinant factors that become obstacles in the implementation of investment in South Sulawesi Province are; (1) The number of Actors involved, both at the central and provincial and district/city levels, making communication in decision-making more complicated, (2) The inherent complexity of investment, which includes financing, procurement of machinery, procurement of raw materials and land acquisition, (3) The level of decision-making that is too long at the trilateral level and at the interchem level, both in the granting of principle licences, recommendations from relevant technical departments, licences to grant fiscal and non-fiscal facilities, both at the central, provincial and regency/municipal levels, (4) Time and leadership changes, changes in leadership (President, Minister, Governor and Regent/Mayor) resulting in policy changes and legal uncertainty.